Physiological traits associated with reductions in grain number in wheat and barley under waterlogging - de San Celedonio, Romina Paola (2018)
Aims Negative effects of waterlogging on wheat and barley yield are expressed mainly through reductions in grain number per plant. Physiological traits associated with reductions in grain number of wheat and barley plants waterlogged at different growth stages during preanthesis were evaluated. Methods Two pot experiments were carried out under contrasting environments, where wheat and barley plants were exposed to waterlogging at four different ontogenic stages, from emergence to anthesis. Physiological traits associated with grain number determination were measured at anthesis and at physiological maturity. Results Waterlogging occurring during the spike growth period significantly reduced grain number per plant up to 70% in wheat and 60% in barley. Reductions in grain number per plant in wheat were mainly related to decreases in grain number per spike, while in barley grain number reductions were related to decreases in the number of spikes. In both species waterlogging produced spike growth reductions that were associated with reductions in the number of fertile florets per spike, without effects on fruiting efficiency. Conclusions The effect of waterlogging on grain number per plant differed between wheat and barley. Waterlogging reduced grain establishment in wheat by affecting the growth capacity of spikes and, consequently, reducing the number of fertile florets per spike. In barley, the main effect of waterlogging was through reductions in the number of spikes per plant, without significant changes in grain number per spike. These differences between species open ways to analyze the impact of different management practices (i.e. nitrogen fertilization, plant population) as alternative to mitigate the negative effect of waterlogging on grain yield.